2016
DOI: 10.1016/j.neuropsychologia.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of early visual word processing – Early versus late N1 sensitivity in children and adults

Abstract: In the course of reading development children become familiar with letter strings and learn to distinguish between lexical and non-lexical items. In previous studies, the N1 component of the ERP was shown to reflect print tuning but also to be sensitive to lexical effects. It remains unclear, however, whether these two aspects of orthographic processing occur at the same time or in different time windows during the lengthy N1 component. Moreover, it is unclear whether these processes develop late or occur alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 85 publications
6
37
1
Order By: Relevance
“…In this study, we refrained from testing coarse neural tuning for print, as indexed by differences in amplitudes between letter and symbols strings (therefore, symbols were not included in the material). Robust print tuning effects in the visual N1 have already been demonstrated elsewhere, at the group (e.g., Maurer et al., 2006, 2007; Brem et al., 2009; Araújo et al., 2012) and individual level (Eberhard-Moscicka et al., 2016). However, studies do not agree in finding differences between different kinds of letter strings such as lexicality and frequency effects.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In this study, we refrained from testing coarse neural tuning for print, as indexed by differences in amplitudes between letter and symbols strings (therefore, symbols were not included in the material). Robust print tuning effects in the visual N1 have already been demonstrated elsewhere, at the group (e.g., Maurer et al., 2006, 2007; Brem et al., 2009; Araújo et al., 2012) and individual level (Eberhard-Moscicka et al., 2016). However, studies do not agree in finding differences between different kinds of letter strings such as lexicality and frequency effects.…”
Section: Discussionsupporting
confidence: 61%
“…But again, lexicality effects on N1 have not been reliably found in children (Kast et al., 2010; Araújo et al., 2012; Hasko et al., 2013; Eberhard-Moscicka et al., 2015). All together, these results seem to suggest that N1 sensitivity to word frequency and lexicality depends on the phase of reading development, as well as on reading expertise (Araújo et al., 2015; Eberhard-Moscicka et al., 2015, 2016). However, in other studies, neither adults nor children processed pseudowords differently than words in the N1 component (Maurer et al., 2005b) or adults did not exhibit a N1 specialization for words over pseudowords in contrast to children who showed larger amplitudes for words (Maurer et al., 2006).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Xue, Jiang, Chen, and Dong () showed that the N1 lexicality effect is also modulated by factors such as familiarity of the script and stimulus length. Recently, Eberhard‐Moscicka, Jost, Fehlbaum, Pfenninger, and Maurer () found that the first and the second subcomponent of the N1 are sensitive to course print tuning in children, whereas in adults only the first subcomponent is sensitive to course print tuning and the second subcomponent is sensitive to the lexicality effect, but only in the participants' native language German and not in the second language English. Zhao et al () found that the N1 was larger in response to words than consonant strings among 7‐year‐old readers with a high reading ability in contrast to readers with a low reading ability.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, mean amplitude was calculated for time windows defined based on the group mean peak latencies (± 2 standard deviations (SD)) of the individually set P1 (Cz–Fz: 43–79 ms; Cz–AvgRef: 43–79 ms), N1 (Cz–Fz: 87–147 ms; Cz–AvgRef: 88–148 ms), and P2 (Cz–Fz: 210-302 ms; Cz–AvgRef: 220–300 ms) markers (n = 222) of the difference channels. In addition, time windows for specific SEP components were chosen in an unbiased way independent from specific channels (Albrecht et al 2005 ; Eberhard-Moscicka et al 2016 ; Meyer et al 2007 ) using the global field power (GFP) as a global measure of the map strength (root mean square of all voltages in a map) representing the SD across all channels (Fig. 2 d).…”
Section: Methodsmentioning
confidence: 99%